The sulphated polysaccharide compounds from green algae (Ulva lactuca L) as a potential natural anti-inflammatory agent based on molecular docking study targeting cyclooxygenase-2 receptor - Dwi Utami; Rezza Wahyudi; Wahyu Widyaningsih (Universitas Ahmad Dahlan, 2023)
The rare sulphated polysaccharides of green algae have been explored of several activities such as antioxidant, anti-inflammation, anti-bacterial, and anti-virus. Ulva lactuca L is one of the majoring algae species in Indonesia that promosing to be explored as natural anti-inflammation in the inflammation disorders treatment. The purpose of this study was to conduct an in-silico test of anti- inflammatory potency of sulphated polysaccharide chemical constituent of green algae (Ulva lactuca L) against the cyclooxygenase-2 enzyme. The methods used were the preparation of a protein structure database cyclooxygenase-2 enzyme (4COX), protein preparation using the Biovia Discovery Studio application, molecular docking simulation of sulphated polysaccharide compounds on proteins using the Autodock 4.0 application and visualization using Ligpot+ v2.2. The results of docking sulphated polysaccharide compounds with the cyclooxygenase-2 enzyme, showed a best binding affinity energy of Gluconic acid ulvan -7.62 kcal/mol similar to the control drug sodium diclofenac (-7.81 kcal/mol), followed by Iduronic acid Ulvan -7.57 kcal/mol, Fucoidan (-6.11 kcal/mol), Alpha Carrageenan (-6.93 kcal/mol), and Lambda Carrageenan (-5.38 kcal/mol). In the conclusion based on the molecular docking result, the sulphated polysaccharide compounds in Ulva lactuca L are potential to be developed as natural antiinflammatory agent by in vitro and in vivo investigation